Investigation of Strain-Induced Precipitation of Niobium Carbide in Niobium Micro-Alloyed Steels at Elevated Temperatures - Tzu-Ching Tsao; Po-Han Chiu; Chien-Yu Tseng; Cheng-Lin Tai; Hsueh-Ren Chen; Tsai-Fu Chung; Chih-Yuan Chen; Shing-Hoa Wang; Yu-Ting Tsai; Jer-Ren Yang (Metals, 2022)
Two steels with a base composition of Fe-0.2C-0.8Mn-1.2Cr (wt%) but with different niobium (Nb) contents (0.02 and 0.03 wt%) were employed to study the effect of precipitate evolution on the softening resistance in the austenite region under elevated temperature deformation. The thermomechanical procedure was executed by a deformation-dilatometer and involved double deformation processes with 25% strain at a 0.25 s−1 strain rate at 900, 925, 950, and 1000 °C. The softening ratios, reflecting the competition between recrystallization and precipitation, were evaluated. The results indicated that both steels showed better softening resistance at 900 °C than at other temperatures. However, the softening ratio of 0.03 wt% Nb-containing steel (Steel 3N) rose after 100 s at 900 °C, while 0.02 wt% Nb-containing steel (Steel 2N) maintained a low softening ratio within 300 s at 900 °C, indicating that Steel 3N was relatively non-durable. A microstructural characterization showed that in the Steel 3N sample deformed at 900 °C, recrystallization occurred more strongly than for Steel 2N after a 1000 s holding time. A follow-up analysis then showed that Steel 3N treated at 900 °C revealed a faster coarsening of the carbides than Steel 2N even in the early stage of precipitation, evidencing that Steel 2N exhibited a lower softening resistance at 900 °C.